The decomposition of neutron-antineutron oscillation operators - Shao-Long Chen; Yu-Qi Xiao (Journal of High Energy Physics, 2023)
Abstract We study the systematic decomposition of the dimension nine neutron-antineutron oscillation operators at tree and one-loop levels. We discuss the topologies’ generation and the assignment of the chiral quarks. The completed lists of the decompositions are provided. We furthermore show an example that the neutron-antineutron oscillation occurs at one-loop level, with the tiny neutrino mass being generated via the scotogenic model and proton decay being evaded.